Percutaneous compression plate versus dynamic hip screw for treatment of intertrochanteric hip fractures: A overview of systematic reviews and update meta-analysis of randomized controlled trials. (September 2016) - Long, Haitao; Lin, Zhangyuan; Lu, Bangbao; Zhao, Ruibo; Sun, Buhua; Cheng, Liang; Zhao, Shushan; Zhu, Yong
Abstract: Purpose: Intertrochanteric hip fractures lead to high morbidity and mortality rates. As a minimally invasive technique, many studies reported the efficacy of PCCP for the treatment of intertrochanteric fractures, but the controversy still existed in some outcomes. The purpose of this study was to evaluate the efficacy of PCCP and DHS by a overview of systematic reviews and well-designed, comprehensive update meta-analysis. Methods: PUBMED, SCOPUS, CCRCT, WANFANG and CNKI database were searched in all languages published up to April 2016. Systematic reviews and randomized controlled trials reporting outcomes of PCCP and DHS for intertrochanteric fractures were included. Meta-analyses comparing the two techniques were performed according to the Cochrane Handbook. Results: Five original trials and four systematic reviews met the inclusion criteria. Meta-analyses showed that the blood loss [SMD = −2.35, 95%CI(−4.26–−0.44)], transfusion volume [SMD = −0.26, 95%CI(−0.47–−0.06)] and complications [RR = 0.33, 95%CI(0.14–0.77)] was statistically less in PCCP group than DHS group while there was no significant difference between two groups in mortality rate, transfusion rate and length of hospital day. Conclusions: PCCP is recommended to treat intertrochanteric hip fractures as an alternative minimally invasive method. More high-quality, randomized controlled trials that are adequately powered are needed to further evaluate the efficacy of PCCP and DHS. Highlights: Compared with DHS, PCCP significantly decreased the blood loss, transfusion volume and complications. PCCP can be used to treat intertrochanteric hip fractures as an alternative minimally invasive method. More high-quality RCTs are needed to further evaluate the efficacy of PCCP and DHS.